An inorganic-rich but LiF-free interphase for fast charging and long cycle life lithium metal batteries - Muhammad Mominur Rahman; Sha Tan; Yang Yang; Hui Zhong; Sanjit Ghose; Iradwikanari Waluyo; Adrian Hunt; Lu Ma; Xiao-Qing Yang; Enyuan Hu (Nature Communications)
Abstract Li metal batteries using Li metal as negative electrode and LiNi1-x-yMnxCoyO2 as positive electrode represent the next generation high-energy batteries. A major challenge facing these batteries is finding electrolytes capable of forming good interphases. Conventionally, electrolyte is fluorinated to generate anion-derived LiF-rich interphases. However, their low ionic conductivities forbid fast-charging. Here, we use CsNO3 as a dual-functional additive to form stable interphases on both electrodes. Such strategy allows the use of 1,2-dimethoxyethane as the single solvent, promising superior ion transport and fast charging. LiNi1-x-yMnxCoyO2 is protected by the nitrate-derived species. On the Li metal side, large Cs+ has weak interactions with the solvent, leading to presence of anions in the solvation sheath and an anion-derived interphase. The interphase is surprisingly dominated by cesium bis(fluorosulfonyl)imide, a component not reported before. Its presence suggests that Cs+ is doing more than just electrostatic shielding as commonly believed. The interphase is free of LiF but still promises high performance as cells with high LiNi0.8Mn0.1Co0.1O2 loading (21 mg/cm2) and low N/P ratio (~2) can be cycled at 2C (~8 mA/cm2) with above 80% capacity retention after 200 cycles. These results suggest the role of LiF and Cs-containing additives need to be revisited.